2023
DOI: 10.3928/01477447-20230104-08
|View full text |Cite
|
Sign up to set email alerts
|

“Fragment Width Ratio” as a Predictor of Nonunion for Femoral Shaft Fracture With Third Fragments

Abstract: Previous studies have reported that large fracture fragment with displacement might cause nonunion of femoral shaft fractures. We therefore intended to delineate significant risk factors for developing a nonunion predisposed by a major fracture fragment. We analyzed 61 patients who were operated on using interlocking nails for femoral shaft fractures from 2009 to 2018. We classified patients with modified Radiographic Union Scale for Tibia fractures scores of less than 11 or needing reoperations by 1 year post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Lee et al 38 reported that both the size (80-mm cut-off) and displacement (proximal, 20-mm cut-off; distal, 10-mm cut-off) of the third fragment were risk factors for non-union and concluded that the fragment displacement angle had a greater influence on the union rate than the size. Conversely, Hamahashi et al 39 reported that displacement of the third fragment was the only risk factor for delayed union, and Lin et al 40 demonstrated that the fragment width ratio could predict non-union for femoral shaft fractures with the third fragment (0.55 cut-off). These studies analysed the characteristics of the third fragment that can affect fracture union in AO/OTA 32B2 fractures according to the importance of fracture morphology and reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 38 reported that both the size (80-mm cut-off) and displacement (proximal, 20-mm cut-off; distal, 10-mm cut-off) of the third fragment were risk factors for non-union and concluded that the fragment displacement angle had a greater influence on the union rate than the size. Conversely, Hamahashi et al 39 reported that displacement of the third fragment was the only risk factor for delayed union, and Lin et al 40 demonstrated that the fragment width ratio could predict non-union for femoral shaft fractures with the third fragment (0.55 cut-off). These studies analysed the characteristics of the third fragment that can affect fracture union in AO/OTA 32B2 fractures according to the importance of fracture morphology and reduction.…”
Section: Discussionmentioning
confidence: 99%